1994
DOI: 10.1523/jneurosci.14-12-07319.1994
|View full text |Cite
|
Sign up to set email alerts
|

The T alpha 1 alpha-tubulin promoter specifies gene expression as a function of neuronal growth and regeneration in transgenic mice

Abstract: We have previously demonstrated that one member of the alpha-tubulin multigene family, termed T alpha 1 in rats, is regulated as a function of neuronal growth and regeneration. To elucidate the molecular mechanisms responsible for coupling gene expression to morphological differentiation, we have isolated the T alpha 1 gene, have fused 1.1 kb of the 5' flanking region to a nuclear lacZ reporter gene, and have generated transgenic mice. Analysis of these transgenic mice demonstrated that marker gene expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
166
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(179 citation statements)
references
References 38 publications
13
166
0
Order By: Relevance
“…37, 38 We constructed first-generation RAd vectors expressing Gli1 or the control marker gene lacZ with a nuclear localization signal. A diagram illustrating the construction of the RAds and the molecular analysis of the recombinant genomes is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…37, 38 We constructed first-generation RAd vectors expressing Gli1 or the control marker gene lacZ with a nuclear localization signal. A diagram illustrating the construction of the RAds and the molecular analysis of the recombinant genomes is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…We utilized the Ta1 promoter element that has been shown to mediate neuronal-specific expression in transgenic animals and in neurons in vitro. 37,38,45,46 To determine whether the Ta1 promoter would retain its neuronal-specific pattern of expression within the context of an adenoviral vector, we constructed a recombinant adenoviral vector where Ta1 was cloned upstream of the gene encoding b-galactosidase containing a nuclear localization signal. Double labeling of neurons following the injection of the Ta1-lacZ vector into the striatum indicated that more than 95% of cells transduced and expressing the reporter gene also expressed the neuronal marker Neu-N indicating the neuronal phenotype of transduced cells.…”
Section: Discussionmentioning
confidence: 99%
“…The fusion protein contains the extracellular ligand-binding and transmembrane domains of mouse EphA5, as well as the GFP coding sequence. The entire fusion gene was then cloned into the P253 vector kindly provided by Freda Miller (Montreal Neurological Institute, Montreal) under the transcriptional control of a neuron-specific ␣-tubulin promoter (27).…”
Section: Generation Of Transgenic Mice Expressing Epha5 Dominant-negamentioning
confidence: 99%
“…9 As lentiviral vectors cannot accept large genetic sequences (up to 10 kb between the long terminal repeats), we selected relatively small promoters. In the present study, we used five kinds of neuron-specific promoters; human synapsin I (SYN), 10 mouse calcium/ calmodulin-dependent protein kinase II (CaMKII), 11 rat tubulin alpha I (Ta1), 12 rat neuron-specific enolase (NSE) 13 and human platelet-derived growth factor-beta chain (PDGF) promoters. 14 Although these promoters are known to be specific for neuronal expression, the transcriptional activities are much weaker than those of viral promoters such as CMV promoter.…”
Section: Introductionmentioning
confidence: 99%